A new self-desalting solar evaporation system based on a vertically oriented porous polyacrylonitrile foam. Issue 24 (3rd June 2019) - Zhang, Qian; Yang, Hongjun; Xiao, Xingfang; Wang, Han; Yan, Lei; Shi, Zhuoxun; Chen, Yali; Xu, Weilin; Wang, Xianbao
Abstract : A new self-desalting evaporation system comprising reduced graphene oxide/cotton fabric and a vertically oriented porous polyacrylonitrile film exhibited excellent self-desalting performance and high photothermal performance. Abstract : Salt accumulation on photothermal layers significantly complicates the operation of solar evaporation systems by decreasing evaporation efficiency and resulting in unstable desalination performance. Despite numerous efforts directed at the development of salt-resistant solar steam generation devices, the challenge of preventing salt accumulation on the photothermal layer while simultaneously maintaining durability, portability, and high photothermal performance isn't yet solved. Herein, we propose a new self-desalting solar evaporation system comprising reduced graphene oxide (RGO)/cotton fabric on a vertically oriented porous polyacrylonitrile foam (VOPPF), demonstrating that no accumulation of salt occurred on the surface of the RGO/cotton fabric in simulated seawater (3.5 wt% NaCl) during 12 h desalination. Moreover, under simulated solar illumination, an extreme amount of salt (2 g NaCl) placed on the RGO/cotton fabric was fully rejected in simulated seawater (after 90 min). The hydrophilicity of the cotton fabric, floatability of VOPPF in water, and continuous water pumping promoted the re-dissolution of salt hindering its accumulation on the photothermal layer during desalination. Simultaneously, the intrinsic features of the RGO/cotton fabric (high durability, portability, and high light absorption efficiency) and VOPPF (low thermal conductivity along the channel direction) allowed for a remarkably high photothermal performance (a clean water production rate of ∼4.0 L m −2 d −1 ) under one sun illumination. Therefore, the developed evaporation system was sufficiently efficient, stable, and portable for direct solar desalination.